استخدام وسيلة السكاربيل لترقية المفردات اللغة العربية لدى الطلبة في معهد بستان العلوم إلأ دايا لنتانج سومنب - Hoirun Nahdiyah; Badriyatus Syamsiyah (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
This research is an experimental research using a quantitative approach. This study aims to determine the application of Scrabble media in learning Arabic for students at the Bustanul Ulum Islamic Boarding School, as well as to determine the increase in students' vocabulary after using Scrabble media. The subjects of this study were the students of the Bustanul Ulum Ellak Daya Islamic boarding school, who took a sample of 14 students. The instruments in this study were observation sheets, pre-test and post-test questions, and documentation. Based on the results of data analysis showed that the average pre-test score was 66.43 and the post-test was 76.79, meaning that there was an increase in student scores of 10.36. As for knowing the effect of applying scrabble media on increasing vocabulary, t-test analysis was used. With the help of SPSS 16.0 software for windows, a t-count of -12,588 was obtained with a P value (significance) of 0.000. This figure shows that t count > -t table (12,588 > 2,650). The t-count curve and t-table show that the t-count that is in the Ho area is rejected, thus Ha is accepted. This shows that the application of scrabble media has an effect on increasing the Arabic language vocabulary of the Santri Pondok Pesantren Bustanul Ulum in Ellak Daya Lenteng Village, Sumenep.